Analisis Perhitungan Dan Perbaikan Tingkat Produktivitas Pada Area Servis Tabung Gas Menggunakan OMAX - Wicaksono, Arif; Zaqi Al Faritsy, Ari (Cosmic Jurnal Teknik, 2024)
Abstract Productivity Productivity is an important factor to support company sustainability. This can be known by analyzing and evaluating output based on the level of work performance during a certain period. PT Petrogas Prima Services is a limited liability company which operates in the field of repair and maintenance services for 3kg LPG gas cylinders. PT Petrogas Prima Servis offers services such as Reset, Repair and Repaint. The entire gas cylinder servicing process is carried out according to the Standard Operating Procedure (SOP) in collaboration with PT. Pertamina (Persero). With distribution management, professional collaboration, and well-controlled and programmed service methods. Productivity measurement is carried out using the Objective Matrix (OMAX) method. The problem that occurs at PT Petrogas Prima Servis is in the gas cylinder service area. This is known to be due to the decline in service results in 2021 with the total results obtained being 933,089 3Kg LPG gas cylinders. Meanwhile, the planning target that must be met in one year is 1,060,328 3Kg LPG gas cylinders. This caused the service yield rate for gas cylinders to decrease by 13.6% or the equivalent of 127,239 gas cylinders. This causes less stability in the gas cylinder service performance process. It is necessary to measure productivity levels to find out what and how causes the lack of decreased gas cylinder service results. The problem identification method uses the Fishbone Diagram and 5W-1H. This method is to find out the causes of decreased productivity in the gas cylinder service area department. These factors are caused by the workforce and work environment. Meanwhile, from the results of calculating the achievement score for each ratio, it is known that the lowest value is ratio 3, namely Labor Effectiveness with a score of 46 with an average of 3.38 which can be seen from the period July to December. The level of significant decline in the value of the productivity index starting from July 193% to September 83%, it can be seen that the decline in the productivity value index reached 110%. This causes a very significant reduction in the number of gas cylinder service output results. Keywords: Objective Matrix (OMAX), Productivity, Fishbone Diagram.